Learning profiles for noninvasive transcutaneous Doppler ultrasound. (April 2015) - Chan, Cangel P.Y.; Li, Yan-Ling; Agarwal, Nandini; Sin, King-Keung; Leung, Yuk-Ki; Narain, Sangeeta; Cheung, Pui-Ling; Tse, Mandy M.; Goggins, William B.; Graham, Colin A.; Rainer, Timothy H.
Abstract : Objective: This study aimed to establish learning profiles for noninvasive transcutaneous Doppler ultrasound. Materials and methods: Four trainees attended a 2-h lecture, followed by a 15-min demonstration on a volunteer and a 30-min hands-on workshop in a small group setting. Then, they underwent hands-on practice on 50 participants without supervision. The skill acquisitions in terms of signal magnitude, signal quality, and measurement time of the trainees were evaluated through 50 assessments, and were compared with that of a trainer with extensive experience on the use of an ultrasonic cardiac output monitor acting as a 'gold standard'. The learning profile for each individual trainee was analyzed using the cumulative sum graphical method. Results: Four trainees performed ultrasonic cardiac output monitor on 50 participants. All trainees attained proficiency after 18–36 assessments to achieve aortic signal magnitude and quality comparable with the trainer. It requires a minimum of nine assessments to obtain three aortic scans within 5 min with 95% success rates. Only half of the trainees achieved competence in pulmonary scans and the minimum number of assessments required was 36. A minimum of 22 assessments were required for three pulmonary scans within 10 min with 95% success rates. Conclusion: A substantial period of learning needs to be undertaken to achieve proficiency on the use of noninvasive transcutaneous Doppler ultrasound. Cumulative sum analysis is a useful tool for ongoing quality assessment during medical education and training in practical procedures on an individual basis. Abstract : Supplemental Digital Content is available in the text.